Remote Ischemic Conditioning: A Novel Non-Invasive Approach to Prevent Post-Stroke Depression - Zhao, Wenbo; Jiang, Fang; Zhang, Zhen; Zhang, Jing; Ding, Yuchuan; Ji, Xunming (Frontiers in Aging Neuroscience, 2017)
Post-stroke depression (PSD) is a common neuropsychiatric complication of stroke. However, due to the high expense and side effects of pharmacotherapy and the difficult-to-achieve of psychotherapy, the prevention and treatment of PSD are still far from satisfaction. Inflammation hypothesis is now playing an essential role in the pathophysiological mechanism of PSD, and it may be a new preventive and therapeutic target. Remote ischemic conditioning (RIC) is a non-invasive and easy-to-use physical strategy, which has been used to protect brain (including ischemic and hemorrhagic stroke), heart and many other organs in clinical trials. The underlying mechanisms of RIC include anti-inflammation, anti-oxidative stress, immune system regulation and other potential pathways. Our hypothesis is that RIC is a novel approach to prevent PSD. The important implications of this hypothesis are that (1) RIC could be widely used in clinical practice to prevent PSD if our hypothesis were verified; (2) RIC would be thoroughly explored to test its effects on other neurobehavioral disorders (e.g. cognitive impairment).